Determination of Factor XIII Activity and of Factor XIII Inhibitors Using an Ammonium-Sensitive Electrode - Hellstern, P; Schilz, K; von Blohn, G; Wenzel, E (Thrombosis and Haemostasis, 1983)
An assay for rapid factor XIII activity measurement has been developed based on the determination of the ammonium released during fibrin stabilization. Factor XIII was activated by thrombin and calcium. Ammonium was measured by an ammonium-sensitive electrode. It was demonstrated that the assay procedure yields accurate and precise results and that factor XIII-catalyzed fibrin stabilization can be measured kinetically. The amount of ammonium released during the first 90 min of fibrin stabilization was found to be 7.8 ± 0.5 moles per mole fibrinogen, which is in agreement with the findings of other authors. In 15 normal subjects and in 15 patients suffering from diseases with suspected factor XIII deficiency there was a satisfactory correlation between the results obtained by the “ammonium-release-method”, Bohn’s method, and the immunological assay (r1 = 0.65; r2= 0.70; p<0.01). In 3 of 5 patients with paraproteinemias the values of factor XIII activity determined by the ammonium-release method were markedly lower than those estimated by the other methods. It could be shown that inhibitor mechanisms were responsible for these discrepancies.
Keywords: Factor XIII activity; Inhibitors of fibrin stabilization; Ammonium release; Ammonium-sensitive electrode